Subnuclear localization, rates and effectiveness of UVC-induced unscheduled DNA synthesis visualized by fluorescence widefield, confocal and super-resolution microscopy - Pierzyńska-Mach, Agnieszka; Szczurek, Aleksander; Cella Zanacchi, Francesca; Pennacchietti, Francesca; Drukała, Justyna; Diaspro, Alberto; Cremer, Christoph; Darzynkiewicz, Zbigniew; Dobrucki, Jurek W. (Cell cycle (Georgetown, Tex.), 2016)
Unscheduled DNA synthesis (UDS) is the final stage of the process of repair of DNA lesions induced by UVC. We detected UDS using a DNA precursor, 5-ethynyl-2'-deoxyuridine (EdU). Using wide-field, confocal and super-resolution fluorescence microscopy and normal human fibroblasts, derived from healthy subjects, we demonstrate that the sub-nuclear pattern of UDS detected via incorporation of EdU is different from that when BrdU is used as DNA precursor. EdU incorporation occurs evenly throughout chromatin, as opposed to just a few small and large repair foci detected by BrdU. We attribute this difference to the fact that BrdU antibody is of much larger size than EdU, and its accessibility to the incorporated precursor requires the presence of denatured sections of DNA. It appears that under the standard conditions of immunocytochemical detection of BrdU only fragments of DNA of various length are being denatured. We argue that, compared with BrdU, the UDS pattern visualized by EdU constitutes a more faithful representation of sub-nuclear distribution of the final stage of nucleotide excision repair induced by UVC. Using the optimized integrated EdU detection procedure we also measured the relative amount of the DNA precursor incorporated by cells during UDS following exposure to various doses of UVC. Also described is the high degree of heterogeneity in terms of the UVC-induced EdU incorporation per cell, presumably reflecting various DNA repair efficiencies or differences in the level of endogenous dT competing with EdU within a population of normal human fibroblasts.